VD_FINDINFO AM 53/10 - 26/2011 vom 21. März 2011 - VD Tribunal cantonal (2011)
PRIME D'ASSURANCE-MALADIE, POURSUITE POUR DETTES, SOLDE DE LA DETTE, FRAIS DE POURSUITE, FRAIS DE SOMMATION | 86 CO, 87 CO